Local tissue damage induced by BaP1, a metalloproteinase isolated from Bothrops asper (Terciopelo) snake venom - Rucavado Romero, Alexandra (1995)
The pathogenesis of hemorrhage and other local effects induced by the metalloproteinase BaP1, isolated from Bothrops asper venom, was investigated using various in vivo and in vitro models. Upon intramuscular injection in mice BaP1 caused rapid hemorrhage in muscular and adipose tissues. Vital microscopy using mouse cremaster muscle evidenced the formation of multiple hemorrhagic foci of an explosive character, originating from capillaries and small venules. In contrast to crude B. asper venom, which besides hemorrhage also induced myonecrosis and thrombosis, vital microscopy detected only hemorrhage after application of BaP1, during the 40-min observation period. However, histological observation in mouse gastrocnemius muscle evidenced a few areas of limited myonecrosis was followed by an incomplete regenerative response, since regenerating muscle fibers were interspersed with fibrosis in some areas. Metalloproteinase BaP1 was not cytotoxic to human and murine endothelial cells in culture, causing only a mild detachment from the culture plate. BaP1 hydrolyzed types I and IV collagen, fibronectin, and laminin upon incubation with these extracellular matrix proteins in vitro. These results suggest that hemorrhage induced by BaP1 is due primarily to the proteolytic degradation to basement membrane components of microvessels and that endothelial cell disruption may be a secondary event. It is concluded that, in addition to hemorrhage, BaP1 contributes to the local tissue damage caused by the venom by inducing myonecrosis, inflammation, and extracellular matrix alterations.